2015
DOI: 10.3727/096368915x686959
|View full text |Cite
|
Sign up to set email alerts
|

The Antisenescence Effect of Trans-Cinnamaldehyde on Adipose-Derived Stem Cells

Abstract: As assuring cell quality is an essential parameter for the success of stem cell therapy, the impact of various senescence-inducing stress signals, and strategies to circumvent them, has been an important area of focus in stem cell research. The aim of this study was to demonstrate the capacity of Trans-cinnamaldehyde (TC) in reversing stress-induced senescence and maintaining the quality of stem cells in a chemically (H2O2)-induced cell senescence model. Because of the availability and the promising applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…These observations were all corroborated by results obtained from our analysis of SA β-Gal activity after 24, 48 and 72 h from the end of the H 2 O 2 treatment, where both hASCs and hWJ-MSCs showed an increase of the SA β-Gal activity. In particular, the higher senescent effect was evident at 48 h. A similar trend was seen in other researches, although it was obtained at different experimental times 42 - 44 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These observations were all corroborated by results obtained from our analysis of SA β-Gal activity after 24, 48 and 72 h from the end of the H 2 O 2 treatment, where both hASCs and hWJ-MSCs showed an increase of the SA β-Gal activity. In particular, the higher senescent effect was evident at 48 h. A similar trend was seen in other researches, although it was obtained at different experimental times 42 - 44 .…”
Section: Discussionsupporting
confidence: 89%
“…Here, we found that in both cell populations, H 2 O 2 not only inhibited cell proliferation in a dose-dependent fashion, but it also affected the persistence of the anti-proliferative effect after the end of exposure (up to 48 or 72 h) in a manner that was dependent upon the duration (1 or 2 h) of the treatment itself. These results are coherent with the reduction of cell vitality observed in hWJ-MSCs 43 - 45 and hASCs 39 , 42 treated with higher concentrations of H 2 O 2 (until 2000 μM) but at low subcultured passages. We also observed a growth slowdown of cells treated with H 2 O 2 400 μM, and a cell inability to re-plate.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Human telomerase reverse transcriptase (hTERT) is a catalytic subunit of human telomerase (13,14), which provides the reverse transcriptase activity needed to maintain the length of the telomere (15). It has been shown that overexpression of hTERT increases the cell lifespan of ameloblastoma cells (16), human fibroblasts (17), adipose-derived stem cells (18) and endothelial cells (19) in vitro. Several studies have demonstrated that the modification of human MSCs with the hTERT gene generates cells with an improved ability for proliferation and cell renewal that retain their potential to differentiate into osteocytes, adipocytes, chondrocytes and gingival epithelial cell lines (20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Cells were seeded in the Lab-Tek II Chamber Slide System of 8-well plates (Nunc) at 3 × 10 4 cells/well. After 24 h, cells were treated with H 2 O 2 (50,100,150,200 and 400 µM) for 1h. To evaluate senescence, the Galactosidase Detection Kit (Abcam, Cambridge, UK) was used after the end of H 2 O 2 treatment (at 24, 48, or 72 h) according to the fabricator's instructions.…”
Section: Senescence-associated β-Galactosidase Assaymentioning
confidence: 99%